Cost effective solution for effective e-Governance - e-Panchayat - CSR Prabhu
There are various models and solutions of e-Governance in the World. However a cost effective solution is always preferable. An electronic knowledge based system titled ` e- Panchayat' with the active involvement of the stake holders at lowest administrative level was successfully designed developed and being implemented successfully in Andhra Pradesh. Several states such as Uttar Pradesh, North Eastern States, Rajasthan , Maharashtra , Tamilnadu etc., the same project is going to be replicated after due customisation. As the project involves e-Governance right at the grass root level i.e., village level and offers a very cost effective solution. The methodology adopted for implementing the system is novel, cost-effective and self-sustaining. To achieve high efficiency the system harnesses the state-of-the-art Information and Communication Technologies which are highly efficient.